Kdo (kaj) piše o/v slovenskih diplomatskih študijah? - Udovič, Boštjan (Studia Historica Slovenica, 2021)
The article analyses publications in the field of Slovenian diplomatic studies in the scientific journals Teorija in praksa, Družboslovne razprave, Annales – Series Sociologia et Historia, Acta Histriae and Studia Historica Slovenica. The most important finding of this article is that publications in the field of Slovenian diplomatic studies are generally rare (they account for between 1 and 3% of all publications), while articles in the field of the history of Slovenian diplomacy predominate among the publications. This is not surprising, since among Slovenian historians there are only a few who deal with so-called diplomatic/political history. Another observation proves to be correct, namely that publications from the field of diplomatic studies appear in waves mainly in thematic issues of the journals.
Keywords: diplomacija; diplomatske študije; mednarodno pravo; Slovenija; slovenske družboslovne revije; znanstveni časopisi